Bersama Lawan Infeksi: Penyegaran Konsep K3 pada SDM Upaya Menjaga Kebersihan Lingkungan, Pengelolaan Linen, dan Dekontaminasi Alat Medis di Klinik M Limo, Depok - Latipah, Tatu; Siregar, Tatiana; Fadrin, Arla Zitka Ramadhani; Neswari, Firzanah Ardhana; Liana, Fitra; Agustian, Friizy; Andirani, Khayla Fadiyah; Zulfikhar, Mubyar Tanza; Annastasya, Mutiara Ardhia; Zahra, Mutiara; Are, Najwa Nabilla Putri; Rainanda, Raisya Azka; Valerin, Stella Evilia (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Background: Occupational accidents in Indonesian healthcare facilities continue to occur due to inconsistent implementation of Standard Operating Procedures (SOP), particularly in the handling of medical equipment, maintenance of workplace cleanliness, and management of contaminated materials. Methods: This community service program involved 10 clinical staff and included a health education intervention on environmental hygiene, equipment decontamination, and linen management. Pre-test and post-test assessments were administered to measure knowledge improvement, and educational materials were delivered using leaflets and posters. Results: The findings indicate that all respondents (100%) adhered to environmental hygiene procedures, including waste segregation, appropriate use of personal protective equipment, and proper handling of spills and sharp waste. Compliance with equipment decontamination procedures was also high (100%), although 10% of respondents were unaware of the availability of written SOPs. Most respondents performed linen management correctly; however, inconsistencies remained in understanding responsibility for washing and storage. Conclusion: Environmental hygiene was applied optimally, linen management was mostly appropriate despite minor inconsistencies, and equipment decontamination showed strong compliance with established standards. Strengthening written SOPs, regular training, and continuous supervision are recommended to maintain service quality and patient safety.